GST Compliance Simplifying Filing in the Digital Age - Rani, J. Hena Esther; Kalpana, G.; Jagadeesan, P. (Journal of Neonatal Surgery, 2025)
This research article aims to inspect the imminent course of GST regarding information technology with particular attention to streamlining tax return filing online. To build trust between taxpayers and the government while considering taxpayers' morality and responsibility the researcher intends to address these requirements where in today's scenario a current problem is tax evasion and fraudulent billing. The IBM SPSS 23 version was used for data analysis where factor analysis, ANOVA, and independent sampling T-Test were used as the research methodology obtained for this study. This study is descriptive and empirical, where 140 samplings were collected using a convenient sampling method. There is a significant impact on taxpayers' compliance behaviour on their sense of morality, obligation, and trust in government which strongly influences taxpayers while complying with the GST system This research paper originally deals with creating new insights into how simplifying tax compliance in the GSTR portal can satisfy and enhance taxpayer morality and obligation, leading to increased trust in the government. By shedding light on this aspect, the research aims to contribute to the existing body of knowledge in this field.